URGENSI PENERAPAN KLAUSULA EKSONERASI DALAM PRODUK HUKUM YANG DIBUAT OLEH NOTARIS (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to explain how important or urgent the application of the exoneration clause is as a form of self-protection of a notary in carrying out his position in accordance with the law on the position of a notary in which the clause used for notary self-protection against parties who come to a notary who has bad faith or falsify data and so on. This research is normative juridical research, namely research that examines or analyzes based on the sources of legislation and uses a statutory approach and a conceptual approach. The results of this study are the need or urgency to apply an exoneration clause or a notary self-protection clause in carrying out his position so that it is not easy for the parties to report a notary, in which the notary in carrying out his position in accordance with the norms and procedures contained in the law on the position of a notary, especially the authority of a notary who contained in Article 15 of the law on the position of a notary, where the application of the clause is valid as long as the notary has carried out the position according to the procedure and is also agreed upon by the parties who appear before the notary.